Application of Green Accounting Concepts through Accounting Education in Support of Green Economy - Agshari, Zara; Rismawati, Rismamati; Supri, Zikra (E-Jurnal Akuntansi, 2024)
This research aims to investigate the significant influence of the application of green accounting concepts and accounting education in supporting the green economy. This research uses quantitative methods with multiple linear analysis techniques to analyze the data. The population of this study consisted of students from the Faculty of Economics and Business, Muhammadiyah University of Palopo. Research sampling was carried out using the Slovin formula, which resulted in a total sample of 133 respondents. The results of this research significantly show that the application of the green accounting concept has a positive impact on the green economy. Apart from that, accounting education also plays an important role in supporting the green economy. Thus, this research concludes that the application of green accounting concepts through accounting education can make a significant positive contribution in supporting green economic growth. Keywords: Green Accounting; Accounting Education; Green Economy